Uncertainty and Monetary Policy. (March 2017) - Kent, Christopher
Abstract: This article presents three dimensions of uncertainty that policy‐makers face when making policy decisions: data uncertainty, model uncertainty and unexpected events. Data uncertainty relates to both revisions and other measurement problems that imply that data are subject to a degree of 'noise'. Model uncertainty relates to the imperfect knowledge we have on the structure of the economy, including the transmission mechanism of monetary policy and the effect of macroeconomic shocks. Unexpected events or shocks contribute to uncertainty about the future, along with the potential for the structure of the economy to evolve over time, which makes the past a poor guide to the future. The article discusses how these different dimensions of uncertainty can influence monetary policy decisions.